Course instruction : - Spaan, W. P. (Wageningen Agricultural Univ, 1979)
The purpose of the practical work is to investigate: 1) The causes of erosion in the Project Area. 2) The degree of the occuring erosion. 3) The consequenses of the erosion for present and future agriculture. 4) Measures to be taken in order to prevent or to control the erosion both on the field and in the drainage system